Energetics of Technical Integration of 2‐Propanol Fuel Cells: Thermodynamic and Current and Future Technical Feasibility. Issue 8 (22nd June 2022) - Braun, Katharina; Wolf, Moritz; De Oliveira, Ana; Preuster, Patrick; Wasserscheid, Peter; Thiele, Simon; Weiß, Lukas; Wensing, Michael
Abstract : 2‐Propanol/acetone is a promising liquid organic hydrogen carrier system for fuel cell reactions. Herein, six different concepts for a 2‐propanol/acetone fuel cell system are evaluated in MATLAB simulation with respect to their thermodynamic integration and technical feasibility. Four of the concepts use a direct 2‐propanol fuel cell while the other two first release molecular hydrogen from 2‐propanol and subsequently use a hydrogen fuel cell. The presented liquid phase 2‐propanol fuel cell concept is thermodynamically feasible but cannot be realized technically using commercial Nafion membranes, due to membrane dissolution by the 2‐propanol/acetone/water fuel mixture. Gaseous 2‐propanol fuel cells imply a high heating requirement for the evaporation of the fuel. A direct high‐temperature fuel cell using 2‐propanol is thermodynamically feasible because there is less water in the overall system but is not technically feasible because of the esterification of phosphoric acid. A very interesting option is the conversion of gaseous 2‐propanol to pressurized hydrogen in an electrochemical pumping step followed by a hydrogen fuel cell, because here the waste heat of a sufficiently hot hydrogen fuel cell can drive the 2‐propanol evaporation. Abstract : The thermodynamic integration and technical feasibility of different concepts for a 2‐propanol fuel cell system are evaluated. The critical aspects regarding a positive energy balance of the system such as water management, recirculation, and fuel utilization are revealed. The concept of electrochemical 2‐propanol to hydrogen conversion combined with a high‐temperature fuel cell seems to be the one with the highest feasibility.